The War against al-Qaeda : Religion, Policy, and Counter-narratives - Zehr, Nahed Artoul (Book collections on Project MUSE., 2017)
In this original and controversial book Nahed Artoul Zehr explores the theological underpinnings of al-Qaeda and related Islamic movements such as ISIS, demonstrating how this religious narrative has helped transform al-Qaeda from a relatively hierarchical and regional organization to a globalized, decentralized, and diffuse network of networks. Does al-Qaeda reflect an theologically authentic or perverted understanding of Islam? At the same time, Zehr critiques the US military and policy establishment as it attempts to offer counter-narratives to the al-Qaeda phenomenon, counter-narratives that emphasize "good Muslims" v. "bad Muslims" in an attempt to embrace a moderate form of Islam. But according to Zehr this approach is misguided: it is beyond the US government's purview, and beyond its expertise, to make such theological claims about Islam; in fact, the current communications strategy is counterproductive. Better, she argues, to focus on the impact of terrorism and why this is inconsistent with Islam scripture and teaching--which just war theory can help us to do. Zehr concludes by offering policy suggestions and recommendations. One of the novel contributions of the project is an analysis of the work of Mustafa abu Mus' ab al-Suri, author of the leading theoretical and tactical al-Qaeda text, The Global Islamic Resistance Call.